IMPROVING THE SPEAKING ABILITY OF GRADE SEVEN STUDENTS OF SMPN 1 MEPANGA THROUGH ENGLISH MOVIES - Nopiyanti, Suci; Kamaruddin, Abdul; Zamzam, Fadhilah; Mashuri (Journal of Language Testing and Assessment, 2025)
The objective of the study is to find out the effectiveness of the English movie in teaching English speaking to grade seven students of SMPN 1 Mepanga in the academic year 2024/2025. The sample of this pre-experimental research was grading seven students of SMPN 1 Mepanga which consisted of 28 students of the VII D class chosen by using the purposive sampling technique. The data were collected by using a speaking test conducted before and after the treatment, or pre-test and post-test. The data was analyzed by using statistics methods. The result shows that there was a significant improvement in the student’s speaking ability. It was proved by the result of the t-counted (19.13) which was greater than the t-table (1.703) in the significance degree, (0.05). The conclusion of this research indicated that the English movie is effective in teaching English speaking in the classroom and provides a significant effect to improve the students’ speaking ability.